The synthesis and structures of rare earth 2-fluorophenyl- and 2, 3, 4, 5-tetrafluorophenyl-N, N′-bis(aryl)formamidinate complexes. (8th January 2016) - Deacon, Glen B.; Junk, Peter C.; Werner, Daniel
Graphical abstract: A range of rare earth complexes involving fluorinated formamidinato complexes have been synthesised. Crystallisation from either dme or diglyme produced single crystals of all compounds and their X-ray crystal structures were determined. Abstract: Redox transmetallation/protolysis (RTP) reactions between free rare-earth metals (La, Nd, or Yb), Hg(C6 F5 )2, and FFormH (FFormH = N, N ′-bis(2-fluorophenyl)formamidine) in thf afforded four rare-earth complexes: trivalent [La(FForm)3 (thf)2 ]·thf, [Nd(FForm)3 (thf) x ], [Yb(FForm)3 (thf)] (when a slight excess of Yb was used), and divalent [Yb(FForm)2 (thf)2 ] (when a large excess of Yb was used). With the exception of [Yb(FForm)3 (thf)], the complexes did not readily crystallise from thf. However, crystallisation from either dme (La, Yb) or diglyme (Nd), produced single crystals of [La(FForm)3 (dme)], [Yb(FForm)2 (dme)2 ], and [Nd(FForm)3 (diglyme)], respectively. A Nd complex of N, N ′-bis(2, 3, 4, 5-tetrafluorophenyl)formamidine (TFFormH): [Nd(TFForm)3 (dme)], was also prepared by a similar RTP reaction, and was crystallised from dme. Heating the previously reported divalent TFForm complex: [Yb(TFForm)2 (thf)3 ], in either PhMe or diglyme, separated out trace amounts of the trivalent complex [Yb(TFForm)3 (thf)2 ] from PhMe, or the mixed oxidation state, solvent separated ion pair (SSIP) [Yb(TFForm)(diglyme)2 ][Yb(TFForm)4 ] from diglyme. The SSIP complex is the first crystallographically characterised trivalent ytterbium complex coordinating four discrete amidinate ligands.